Reducing workplace burnout: The relative benefits of cardiovascular and resistance exercise - Bretland, Rachel J; Thorsteinsson, Einar B (PeerJ PrePrints, 2014)
Objectives. With 43% of Australians experiencing occupational burnout therapies for burnout reduction are paramount to organisational efficiency. Exercise has potential to provide a multilevel and cost effective burnout intervention. The current study aims to extend the literature by comparing cardiovascular with resistance exercise to assess their relative effectiveness against well-being, perceived stress, and burnout. Design. Participants were 49 (36 females and 13 males) previously inactive volunteers ranging in age from 19 to 68 that completed a four week exercise program of either cardiovascular, resistance, or no exercise (control). Method. Participants were measured against the Subjective Exercise Experience Scale, the Perceived Stress Scale, and the Maslach Burnout Inventory. Results. After four weeks of exercise participants had greater positive well-being and personal accomplishment, and concomitantly less psychological distress, perceived stress, and emotional exhaustion. Cardiovascular exercise was found to increase well-being and decrease psychological distress, perceived stress, and emotional exhaustion. Resistance training was noticeably effective in increasing well-being and personal accomplishment and to reduce perceived stress. Our preliminary findings revealed large effect sizes suggesting that exercise may be an effective treatment for burnout. However, given a small sample size further research needs to be conducted. Conclusion. Different types of exercise may thus help protect against burnout as exercise seems to increase well-being and personal accomplishment while decreasing psychological distress, perceived stress, and emotional exhaustion. Organisations that want to address burnout can assist by improving their employees’ access to regular exercise programs.
Keywords: exercise; cardiovascular; burnout; perceived stress; resistance